Current advances in regulation of bone homeostasis - Abdul Alim Al‐Bari; Abdullah Al Mamun (FASEB BioAdvances, 2020)
Abstract Bone homeostasis is securely controlled by the dynamic well‐balanced actions among osteoclasts, osteoblasts and osteocytes. Osteoclasts are large multinucleated cells that degrade bone matrix and involve in the bone remodelling in conjunction with other bone cells, osteoblasts and osteocytes, the completely matured form of osteoblasts. Disruption of this controlling balance among these cells or any disparity in bone remodelling caused by a higher rate of resorption by osteoclasts over construction of bone by osteoblasts results in a reduction of bone matrix including bone mineral density (BMD) and bone marrow cells (BMCs). The dominating effect of osteoclasts results in advanced risk of bone crack and joint destruction in several diseases including osteoporosis and rheumatoid arthritis (RA). However, the boosted osteoblastic activity produces osteosclerotic phenotype and weakened its action primes to osteomalacia or rickets. On the other hand, senescent osteocytes predominately progress the senescence associated secretory phenotype (SASP) and may contribute to age related bone loss. Here, we discuss an advanced level work on newly identified cellular mechanisms controlling the remodelling of bone and crosstalk among bone cells as these relate to the therapeutic targeting of the skeleton.